Emerging Research Issues and Directions on MaaS, Sustainability and Shared Mobility in Smart Cities with Multi-Modal Transport Systems - Fu-Shiung Hsieh (Applied Sciences)
In recent years, several emerging transport modes have appeared in cities all over the world and have been widely adopted by commuters and travelers. This leads to strong growth and popularity of multi-modal transport and Mobility as a Service (MaaS) in cities. These emerging transport modes have not only received much attention from service providers and practitioners but have also attracted researchers in related communities. These are reflected in the growing number of published papers related to research issues of multi-modal mobility transport in cities. The factors that have been driving the strong growth of the number of published papers related to the emerging multi-modal transport in cities are the deficiencies of effective solution methods to accommodate the needs of users in cities with multi-modal transport modes. Although the existing literature is still deficient in offering seamless end-to-end multi-modal mobility transport services, it provides valuable sources and clues for finding the potential future research subjects/issues/directions. In this study, we attempt to identify potential research directions based on a review of the existing literature on multi-modal mobility transport. By searching the WOS database, we analyze the profile and trends of research directions related to multi-modal mobility. The results of this study pave the way for the assessment of research subjects/issues/directions under the umbrella term of multi-modal mobility transport. This review paper significantly reduces the time required for readers to identify prospective research subjects, issues, or directions without delving into the literature.